Nonexistence of Harberger-Laursen-Metzler Effect with Endogenous Time Preference in an Imperfect Capital Market. (15th July 2015) - Wang, Deng-Shan; Jin, Miao
Abstract : This paper investigates the spending and current-account effects of a permanent terms-of-trade change in a dynamic small open economy facing an imperfect world capital market, where the households' subjective discount rate is a function of savings. Under the assumption that the bond holdings are measured in terms of home goods, it is shown that when the discount rate is a decreasing function of savings, there does not necessarily exist a stable state; however, when the discount rate is an increasing function of savings, a saddle-path stable steady state comes into existence and the Harberger-Laursen-Metzler effect does not exist unambiguously; that is, an unanticipated permanent terms-of-trade deterioration leads to a cut in aggregate expenditure and a current-account surplus. The short-run effects obtained by the technique by Judd (1985, 1987) and Zou (1997) are consistent with the results from the long-run analysis and diagrammatic analysis.